Analisis Kinerja Keuangan Pada Perusahaan Daerah Air Minum (PDAM) Kota Makassar - Randi Tangdialla; Luther P. Tangdialla; Dwi Natalia; Ade Lisa Matasik (Perspektif Akuntansi, 2020)
This study aims to measure and analyze the financial performance of the Municipal Waterworks of Makassar City based on regulation Minister of Home Affairs Indonesia Number 47 of 1999. The data of this study uses secondary data, namely the financial statements from the Municipal Waterworks of the Makassar City in 2015-2017. The method used in this research is quantitative descriptive method. The results show that the measurement of the financial performance of the Municipal Waterworks of Makassar City based on 10 indicators set by the regulation Minister of Home Affairs Indonesia Number 47 of 1999 in 2015 has a financial aspect performance value of 66.67 in the category of "Good", in 2016 it has a performance value of 83 financial aspects 31 in the "Very Good" category and in 2017 it had a performance value of 81.67 in the financial aspect in the "Very Good" category. Therefore, it can show the average value of the performance of the financial aspects of PDAM Makassar City shows a “Very Good” performance with an average value of 77.22.